Analysis of Tooth Surface Error of Topology Modification Gear - Wang Zhonghou; Liu Shaokun; Liu Xinrong; Zhang Liming (Jixie chuandong)
When gear topology modification using the forming method grinding,the tooth profile modification is achieved by trimming the wheel truncation,while the tooth modification is achieved by adding an additional movement of the wheel or gear. But when the gear wheel or wheel there is additional movement,the relative position between gear and grinding wheel will change,the actual contact point of the surface will also be a corresponding change,the tooth modification and tooth profile modification will interfere. Therefore,there is a certain error between the topological modification tooth surface and the theoretical tooth surface. The topological errors are analyzed and discussed through calculation examples. The results show that the variation of center distance is linear to the topological tooth surface error which can guide the topology modification of gear.